Assessing the Readiness Level of Don Honorio Ventura State University - College of Computing Studies Towards the Implementation of Blended Learning - Aileen P. de Leon; Eden D Garcia (Research Synergy Foundation, 2021)
Blended learning (BL) emerged abruptly when global pandemic affected the education system. Significant changes are brought by this model where it optimizes the instructional resources and upscale the quality of learning. This study focused in determining the level of readiness of the state university encompassing the domains of blended learning by stating its pedagogical condition and limitations. As a result, the researchers aim to identify strategic programs that can help the university implement BL effectively. The study combined both quantitative and qualitative research approach where the foremost used descriptive research to describe the characteristics of students and teachers, as well as their perspective towards BL. The latter discussed further the implications of implementing BL through an in-depth interview. The survey was administered to 110 students and 30 teachers, while the interview was conducted to 3 groups. Results indicated that students are in the Intermediate level in terms of ICT skills, while teachers are found to be in the Expert level. The high percentage of stakeholders having ICT skills and means brings a positive perspective towards BL. Moreover, the university’s initiatives to employ BL through academic and administrative capability-building activities and programs, recognition of different roles to be assumed by the key stakeholders and operational guidelines were the key indicators of the readiness of the university.